Keputusan Menjadi Relawan Kandidat Pemimpin Politik - Angelin Stefanny Putri Lantapi; Waluyo Budi Atmoko; Nang Among Budiadi (Manajemen Kreatif Jurnal, 2024)
Political volunteers are the key to a leader candidate's victory in a general election contest. This study aims to predict a person's decision to volunteer for a political candidate. The study examines the influence of religiosity, compassion, political leadership, and self-efficacy on the decision to volunteer. The research was conducted using a survey design with a population of volunteers of a political candidate. A sample size of 200 respondents was collected using purposive sampling technique. Hypotheses were tested using structural equation modeling analysis method. The results of the study found: (1) religiosity affects compassion, (2) religiosity has no effect on volunteering decisions, (3) political leadership has a significant effect on volunteering decisions, (4) efficacy has no effect on volunteering decisions, and (5) compassion has no significant effect on one's decision to volunteer. These results suggest that supporting parties and candidates competing to win elections should develop leadership styles that are acceptable to voters.